PENINGKATAN GAYA BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN JARAK JAUH DI ERA NEW NORMAL - Rabiatul Adawiyah (Jurnal Pendidikan dan Sastra Inggris, 2022)
This study aims to analyze the increase in the transition to distance learning in the new normal era which is able to develop an increase in learning styles for students from various cycles of the learning process. This research uses a qualitative descriptive approach, a qualitative descriptive research type. The findings of this research study are confused with the fact that the success of the teaching and learning process is still doubtful until now, because each student's learning style depends on the arrangement of the class, and the delivery of material from the educator. readiness and competence that teachers need to have to support effective and quality learning in the new normal era during the Covid-19 pandemic.